1997
DOI: 10.1007/s004140050103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of beverages and beverage stains by GC/MS using aroma components as indicators

Abstract: A method to identify brown coloured beverages or beverage stains for criminological purposes was devised using aroma components as indicators. The examined beverages comprised three brands each of beer, coffee, cola and black tea, two brands of oolong tea, and four brands of green tea. Aroma components in each sample were efficiently concentrated with a porous polymer beads column (Porapak Q) and were analyzed by gas chromatography/mass spectrometry (GC/MS) using n-octyl alcohol as the internal standard. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This finding was supported by the previous research which revealed that linalool has the highest FD factor in lemon-lime carbonated beverages. 14 Furthermore, the cooling note of cola could be associated with a higher level of 1,8-cineole (9). The high-potency aroma compounds were also responsible for the other aroma attributes, such as brown spice aroma from eugenol (51) or vanilla note from coumarin (56).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding was supported by the previous research which revealed that linalool has the highest FD factor in lemon-lime carbonated beverages. 14 Furthermore, the cooling note of cola could be associated with a higher level of 1,8-cineole (9). The high-potency aroma compounds were also responsible for the other aroma attributes, such as brown spice aroma from eugenol (51) or vanilla note from coumarin (56).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Despite its popularity, there are only a few studies on the flavor chemistry of cola. Cola aroma has been studied by both sensory and instrumental techniques. Headspace volatiles of decarbonated colas were evaluated by solid-phase microextraction (SPME) and dynamic headspace analysis .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations